Comparison of two intraoperative examination methods for the diagnosis of sentinel lymph node metastasis in clinically early stage endometrial cancer: A Turkish Gynecologic Oncology Group Study (TRSGO-SLN-003). (June 2021) - Taşkın, Salih; Varlı, Bulut; Altın, Duygu; Takmaz, Özgüç; Vatansever, Doğan; Ersöz, Cevriye Cansız; Turan, Hasan; Bulutay, Pınar; Zeren, Handan; Havare, Semiha Battal; Karabük, Emine; Naki, Murat; et al.
Highlights: Presence of macrometastasis in sentinel node is the main predictor of involvement of other nodes. Intraoperative frozen section examination of sentinel node has high sensitivity to identify macrometastasis. Intraoperative sentinel node examination could help the surgeons to decide for systematic lymphadenectomy. Abstract: Objective: This study evaluated diagnostic accuracy of intraoperative sentinel lymph node (SLN) frozen section examination and scrape cytology as a possible solution for management of SLN positive patients. Study design: Clinically early-stage endometrial cancer patients who underwent SLN algorithm and intraoperative SLN examination were analyzed. Findings were compared with final pathology results and diagnostic accuracy of frozen section and scrape cytology were evaluated. Results: Of the 208 eligible patients, 100 patients (48 %) had frozen section examination and 108 (52 %) had scrape cytology of the SLN. Intraoperative examination and final pathology were negative for metastasis in 187/208 (90 %) cases. The rest 21 cases had metastatic SLNs according to final pathology. 12 of 21 (57 %) metastases were classified as macrometastasis. Intraoperative examination of SLNs correctly identified 13 cases (true positive) and missed 8 cases (false negative). Five of 8 false negative cases had micrometastasis or isolated tumor cells. Considering identification of macrometastasis, sensitivity and negative predictive value were 85.71 % and 98.94 %, respectively, for the frozen section and 60.00 % and 98.15 %, respectively, for the scrape cytology. Conclusion: Frozen section examination of SLN has higher sensitivity in detecting macrometastasis compared to scrape cytology and it could help the surgeon in decision for further lymphadenectomy intraoperatively.